PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA PT. ELTEHA CARGO PEKANBARU - Liviesta, Faradina; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the quality of service to customer loyalty at PT. ELTEHA Cargo Pekanbaru. Quality of Service as a Variable (X), and Customer Loyalty as a variable (Y).Method in this research is quantitative with SPSS program, where sample used is consumer of Elteha Cargo counted 100 respondents. The amount can already represent the population. Data collection techniques through questionnaires, and interviews.The result of this research conclude that service quality variable has significant influence to Customer Loyalty.Keywords: Service Quality, Customer Loyalty